Suicide in anaesthetists: a systematic review - Plunkett, E; Costello, A; Yentis, SM; Hawton, K (Wiley, 2021)
Evidence suggests that healthcare professionals are at an increased risk of dying by suicide, with anaesthetists at particularly high risk. However, much of the data on which this is based are historical. With a focus on the epidemiology and methods used, we conducted a systematic review of evidence regarding suicide and suicidal behaviour among anaesthetists to provide a more contemporary summary. The systematic review process was adapted from a previous similar study in veterinary surgeons and was consistent with recommended guidance. We identified 54 articles published in or after 1990 that had anaesthetist-specific data and met the inclusion criteria. Seven of these reported epidemiological data, of which four were published after 2000. Although none of the more recent studies reported standardised mortality rates specific to suicide in anaesthetists, the proportion of anaesthetists dying by suicide was increased with respect to comparator groups, which is consistent with previous findings. Eleven studies that included information on suicidal behaviour reported suicidal ideation in 3.2–25% of individuals (six studies) and suicide attempts in 0.5–2% (four studies). Studies reporting methods of suicide highlighted the use of anaesthetic drugs, particularly propofol, supporting the suggestion that the increased risk of suicide in anaesthetists may be related to the availability of the means. We discuss our findings in relation to other recently published data and guidance concerning mental health problems in anaesthetists.